2022
DOI: 10.1097/mpa.0000000000002081
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Attrition in Intraductal Papillary Mucinous Neoplasms of the Pancreas Associated With Carcinogenesis and Aging

Abstract: Objectives: It is challenging to preoperatively distinguish malignant and benign forms of intraductal papillary mucinous neoplasms (IPMNs) of the pancreas. The aims of this study were to investigate whether telomere length is associated with pathological grade of IPMNs and age and to clarify the utility of telomere length as a marker to identify malignant IPMNs.Methods: Pancreas tissue was obtained from 28 patients after resection.We measured the telomere lengths of tumor cells in IPMNs and normal duct cells b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In PanIN and IPMN, there are many changes in the epithelial cells affected by the disease, one of which is the presence of telomere shortening [33,34]. Other studies have shown that the telomerecentromere ratio (TRC) decreases as the pathological grade of IPMN increases [35]. This suggests that telomeres become progressively shorter as the disease progresses.…”
Section: Telomeres and Precancerous Lesions Of Pancreatic Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In PanIN and IPMN, there are many changes in the epithelial cells affected by the disease, one of which is the presence of telomere shortening [33,34]. Other studies have shown that the telomerecentromere ratio (TRC) decreases as the pathological grade of IPMN increases [35]. This suggests that telomeres become progressively shorter as the disease progresses.…”
Section: Telomeres and Precancerous Lesions Of Pancreatic Cancermentioning
confidence: 99%
“…Its specific anticancer mechanisms include inhibition of HIF-1α、regulation of VEGF/VEGFR-2 signalling pathway that inhibits angiogenesis and selectively stimulates the Gαs/cAMP pathway that inhibits cancer cell proliferation, and so on. However, The NTCR showed a gradual decrease with increasing pathological grade of IPMNs [35] The sample size only includes the number of samples related to pancreatic lesions in the study and the control group.…”
Section: Immunotherapymentioning
confidence: 99%